Development of fibre metal laminate materials for automotive application - Rejab, Mohd Ruzaimi Mat (2018)
Application of fibre metal laminate have found specifically in aerospace industries. Development new material in automotive industry has begun to reduce car crash impact and fuel consumption. Fibre metal laminate was fabricated by using different composite materials such as plain weave carbon fibre reinforced polymer (CFRP), glass fibre reinforced polymer (GFRP), unidirectional prepreg carbon fibre reinforced polymer (CFRP) and self-reinforced polypropylene polymer (SRPP). A compression moulding technique was used to manufactured the fibre metal laminate. Compressive strength of the fibre metal laminate was measured based on variation speed and crosshead speed of low-velocity and quasi-static respectively. Mechanical response of the fibre metal laminate was predicted by using numerical modelling, Abaqus 6.13 version. Finite element analysis result has showed good agreement with experimental measurement. From the experimental result showed that, fibre metal laminate Al/SRPP would potentially become alternative lightweight material as to reduce the concerned issues in automotive industry.